2021
DOI: 10.1155/2021/8575108
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Variation Rule and Characteristics of Pore Water Pressure in the Failure Process of Saturated Rock

Abstract: With the development of tunnels and other engineering constructions into the deep strata, rock masses are more prone to dynamic damage such as rock bursts under in situ conditions and excavation disturbances. The pore water in the rock mass will produce pressure changes during this process. According to the relationship between the change of pore water pressure and the development of rock mass damage, the variation rule and precursor characteristics of pore water pressure in the process of rock mass failure ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…The non-uniform settlement caused by stratum creep and train cyclic load has a significant impact on tunnel structure safety and stability. At present, the backfill materials of expressway tunnel engineering are mainly flake stone concrete and low-strength-grade plain concrete [1][2][3]. Chen Yun [4] used the finite element calculation method by changing the elastic modulus of concrete elements and found that the deformation and stress of the tunnel surrounding rock and the internal force of lining were reduced greatly with the increase in the elastic modulus of backfill concrete at the top of the middle wall.…”
Section: Introductionmentioning
confidence: 99%
“…The non-uniform settlement caused by stratum creep and train cyclic load has a significant impact on tunnel structure safety and stability. At present, the backfill materials of expressway tunnel engineering are mainly flake stone concrete and low-strength-grade plain concrete [1][2][3]. Chen Yun [4] used the finite element calculation method by changing the elastic modulus of concrete elements and found that the deformation and stress of the tunnel surrounding rock and the internal force of lining were reduced greatly with the increase in the elastic modulus of backfill concrete at the top of the middle wall.…”
Section: Introductionmentioning
confidence: 99%